Notes on Mary Berenson's Diary (1891–1893). (3rd April 2017) - Della Monica, Ilaria
Abstract : The diaries that Mary Berenson (1864–1945) kept from 1879 until 1937 are preserved in the Berenson Library and Archive at Villa I Tatti, Harvard University Center for Italian Renaissance Studies in Florence. In them, Mary recorded the travels she undertook with her second husband Bernard Berenson (1865–1959) to visit museums, churches and private collections. She also took notes on books, music and the people they met. Since the diaries represent a potentially important source for many different kinds of research projects, the Biblioteca Berenson plans to make them available in an online edition. This article focuses on the first diary of the series, covering the years 1891–93, and shows how it provides important information on how they developed the concept of connoisseurship. Additional material from the Archive and the Biblioteca Berenson is also presented.